Sustainable supply chain management in a circular economy: Legal barriers, environmental challenges, and a composite performance index - Hussein Abdulhadi Mahdi; Bushra Saadoon Mohammed; Ahmed Fayadh Saleh Hammam; Mujahed Mutlaq AbdulRahman; Baker Mohammed Khalil; Viktor Sukhomlyn (Environment and Social Psychology, 2025)
Sustainable supply chain management (SSCM) is now a priority channel through which the principles of the circular economy are operationalized, but implementation frequently remains crippled by the issue of legal and environmental barriers. This research seeks to assess compliance (sectoral), resource efficiency, waste reduction, and carbon impact (sectoral) and propose a multidimensional Circular Economy Performance Index (CEP) to assess the adoption of sustainability. Mixed-methodology design was used with 15 semi-structured interviews with industry experts and a survey of 120 professionals working in the manufacturing, retail and logistics sectors. The results show that manufacturing shows the most signs of compliance and efficient use of resources due to the established regulatory frameworks and the progressive waste management policies. Retail displays moderate improvement, where consumer compulsion is a driving force but packaging inefficiencies limit the improvement whereas logistics has the lowest performance as the regulatory fragmentation and carbon-intensive operations. These differences are confirmed by the CEP index, where manufacturing is the most developed sector, retail is intermediate, and logistics is the least developed. The findings highlight the fact that legal frameworks, enforcement of regulations and adoption of technology have critical roles in defining the result of sustainability. This study is valuable because it incorporates both legal and environmental aspects into one assessment framework, providing policy-makers with evidence to balance compliance with managers with advice that may help improve performance in the sector. There are such limitations as small sample size and self-reported data, which implies that larger and longitudinal studies and independent validation are necessary. In general, the paper has identified the need of a concerted legal reform, technological development, and participatory governance to promote SSCM in the context of a circular economy.